O problema da filosofia como sistema de pensamento único em "O mundo como vontade e representação de Arthur Schopenhauer" - Uchôas, Pedro Damasceno (Universidade Federal de São Carlos, 2024)
This research has as main goal to analyze and investigate the problem created by Schopenhauer’s explanation of the organization of The world as will and representation According to Schopenhauer, his philosophy, as explained in The world, should be read and understood as the communication of a single thought. In spite of this, he did not mention what explictly is the single thought behind the four divisions of his major work. There remains a question if Schopenhauer’s main work could correspond to a single thought formulated as a single proposition or if the unity of his theoretical enterprise is due to the communality of the themes developed by his main work. Given that, it is necessary to search for the possible solutions to the problem, considering the hypothesis formulated during the research and by commentators in order to verify the possibility of each one of them in order to find the best solution to the problem. It is necessary to consider the fact that language as a tool for survival and Will’s manifestation leads Schopenhauer’s philosophy to problems on the limits of communication and thought and drives it to an innovative stage between science and art. The philosophy of Schopenhauer has to be considered not as a static series of thoughts, but an organism which needs the reader as its counterpart.
The problem of philosophy as a system of single thought in "Arthur Schopenhauer's The world as will and representation"
Keywords: Schopenhauer; Pensamento único; Organismo; Sistematicidade; Single thought; organism; Sistematicity; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA